Enhanced bacterial disinfection by CuI–BiOI/rGO hydrogel under visible light irradiation. Issue 33 (8th June 2021) - Ma, Xi; Wang, Ziwei; Yang, Haoguo; Zhang, Yiqiu; Zhang, Zizhong; Lin, Huaxiang; Long, Jinlin; Wang, Xuxu; Lin, Qun
Abstract : Compared with traditional layered graphene, graphene hydrogels have been used to construct highly efficient visible light-excited photocatalysts due to their particular three-dimensional network structure and efficient electron transport capacity. Abstract : Compared with traditional layered graphene, graphene hydrogels have been used to construct highly efficient visible light-excited photocatalysts due to their particular three-dimensional network structure and efficient electron transport capacity. In this work, CuI–BiOI/rGO hydrogel with excellent photocatalytic antibacterial activity was prepared and its activity against Escherichia coli and Staphylococcus aureus was evaluated. The result indicates that CuI–BiOI/rGO hydrogel exhibits superior sterilization performance and higher stability than CuI–BiOI and BiOI/rGO, and could completely kill Escherichia coli and Staphylococcus aureus within 40 min. However, only a small amount of Escherichia coli and Staphylococcus aureus can be inactivated by CuI–BiOI and BiOI/rGO hydrogels. Graphene hydrogel plays a significant part in enhancing the disinfection activity of CuI–BiOI/rGO hydrogel. Furthermore, the synergistic effect between CuI of p-type semiconductors, as a hole transport layer, and graphene hydrogel greatly increases the separation and transfer efficiency of photogenerated electron holes excited by BiOI, and further improves the disinfection activity of CuI–BiOI/rGO hydrogel.